Volatility models of currency futures in developed and emerging markets - SEQUEIRA, J. M. (Institutional Knowledge at Singapore Management University, 2004)
This paper examines volatility models of currency futures contracts for three developed markets and two emerging markets. For each contract, standard models of the Unbiased Expectations Hypothesis (UEH) and Cost-of-Carry hypothesis (COC) are extended to derive volatility models corresponding to each of the two standard approaches. Each volatility model is formulated as a system of individual equations for the conditional variances of futures returns, spot returns and the domestic risk-free interest rate. The empirical results suggest that the conditional volatility of futures returns for emerging markets is significant in explaining the conditional volatility of returns in the underlying spot market. For developed markets, however, the conditional volatility of the spot returns is significant in explaining the conditional volatility of futures returns. Moreover, it is found that the domestic risk-free interest rate has little impact on the conditional variances of the futures, spot and domestic risk-free interest rates.